2009
DOI: 10.1590/s1413-70542009000700012
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização molecular de cultivares de cana-de-açúcar utilizando marcadores ISSR

Abstract: , Márcia Vanusa da Silva RESUMOA diversidade genética de catorze cultivares de cana-de-açúcar (Saccharum oficinarum) foi acessada por meio de marcadores moleculares ISSR. Objetivou-se caracterizar molecularmente as cultivares estudadas. Foram utilizados trinta e sete primers de ISSR, dos quais, oito foram eficientes na amplificação do DNA das amostras analisadas, sendo sete primers suficientes para distinguir todas as cultivares de cana-de-açúcar envolvidas nas análises. A faixa de amplicons variou de 300 a 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
13
0
3
Order By: Relevance
“…Therefore, this is an efficient method to detect genetic variability within and between populations of T. speciosum. Some authors have reported the successful use of ISSR markers (Almeida et al, 2009;Rossi et al, 2009;Brandão et al, 2011). These markers are efficient, cost-effective, and generate large amount of information.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this is an efficient method to detect genetic variability within and between populations of T. speciosum. Some authors have reported the successful use of ISSR markers (Almeida et al, 2009;Rossi et al, 2009;Brandão et al, 2011). These markers are efficient, cost-effective, and generate large amount of information.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, oligonucleotides were chosen based on them being polymorphic for the varieties of sugarcane tested (Almeida et al, 2009).…”
Section: Molecular Analysismentioning
confidence: 99%
“…Therefore, this method is efficient to detect genetic variability within and between populations of T. subincanum. The usefulness of this type of marker has been previously described for both cultivated and wild species (Rossi et al, 2009;Almeida et al, 2009;Brandão et al, 2011). This marker also presents high reproducibility and potential to be used in species without detailed DNA sequence information (Rossi et al, 2009;Almeida et al, 2009;Brandão et al, 2011).…”
Section: Issr Analyses and Genetic Diversity Within Populationsmentioning
confidence: 99%